He Incidence of mental health on consumer behavior patterns: Analysis of game theory - Erazo Guijarro, Fausto Danilo (2025)
Analysis of the impact of mental health on consumer behavior, using game theory, reveals that consumers' initial willingness to act safely is crucial to achieving secure stability. In comparison, consumers without mental health disorders tend to be somewhat delayed in their strategic choices. The study shows that consumers can be deterred from choosing unsafe behaviors through positive incentives, such as bonuses, and negative incentives, such as fines, with similar sensitivity between the two. Furthermore, when spillover risk loss is effectively controlled, consumers tend to adopt safe behaviors more quickly. These findings offer valuable guidelines for consumer safety management, and practical suggestions are proposed from different perspectives: that of the consumer, that of market members, and that of the safety climate for consumers with mental health disorders. The goal is to reduce unsafe behavior and foster a safe environment, creating a positive cycle of safety. The methodology used in the study combines evolutionary analysis of the game with the evaluation of system stability, providing a solid basis for understanding and addressing this complex dynamic. Ultimately, the study offers a path toward a consumer safety environment that is beneficial to all parties involved.